Edukasi Model Proceed-Precede untuk Meningkatkan Health Literacy Ibu Hamil di Puskesmas Bajeng, Gowa - Nurul Fadhilah Gani; Nurhidayah Nurhidayah; Hasnah Hasnah (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
The literacy ability of pregnant women can support the health of mothers and babies. For this reason, various efforts need to be made to improve the health literacy of pregnant women, one of which is by providing education. This study aims to analyze the effect of the education proceed-precede model in improving the health literacy of pregnant women at the Bajeng Health Center, Gowa Regency. This type of research was experimental with a one group pretest and posttest design. The subjects of this study were 35 pregnant women who made ANC visits at the Bajeng Health Center, which were selected by purposive sampling technique. Data were collected through filling out a health literacy questionnaire from Ishikawa, where health literacy was divided into 3 dimensions, namely functional, critical, and communicative. Data were analyzed using paired sample t-test. The results of the analysis show that there were differences in the average health literacy of pregnant women before and after education, namely: functional literacy = 0.629, communicative literacy = 0.40, and critical literacy = 1.00. The p-value for functional literacy = 0.000, critical literacy = 0.004, and communicative literacy = 0.000. Thus statistically, it was concluded that there was a difference in the health literacy of pregnant women between before and after education. Furthermore, it was concluded that the education proceed-precede model was effective in improving the health literacy of pregnant women, so that it could be used as an intervention of choice in improving the health literacy of pregnant women.Keywords: health literacy; pregnant mother; education; proceed-precede ABSTRAK Kemampuan literacy ibu hamil dapat menunjang kesehatan ibu dan bayi. Untuk itu, perlu dilakukan berbagai upaya untuk meningkatkan health literacy ibu hamil, salah satunya dengan pemberian edukasi. Penelitian ini bertujuan untuk menganalisis pengaruh edukasi model proceed-precede dalam meningkatkan health literacy ibu hamil di Puskesmas Bajeng, Kabupaten Gowa. Jenis penelitian ini adalah eksperimental dengan desain one group pretest and posttest. Subyek penelitian ini adalah 35 ibu hamil yang melakukan kunjungan ANC di Puskesmas Bajeng, yang dipilih dengan teknik purposive sampling. Data dikumpulkan melalui pengisian kuesioner health literacy dari Ishikawa, dimana health literacy terbagi menjadi 3 dimensi yaitu fungsional, kritikal, dan komunikatif. Data dianalisis menggunakan uji paired sample t-test. Hasil analisis menunjukkan perbedaan rerata health literacy ibu hamil sebelum dan setelah edukasi yaitu: literacy fungsional = 0,629, literacy komunikatif = 0,40, dan literacy kritikal = 1.00. Nilai p untuk literacy fungsional = 0,000, literacy kritikal = 0,004, dan literacy komunikatif = 0.000. Dengan demikian secara statistik, disimpulkan bahwa ada perbedaan health literacy ibu hamil antara sebelum dan setelah edukasi. Selanjutnya disimpulkan bahwa edukasi model proceed-precede efektif untuk meningkatkan health literacy ibu hamil, sehingga dapat digunakan sebagai intervensi pilihan dalam peningkatan health literacy ibu hamil.Kata kunci: health literacy; ibu hamil; edukasi; proceed-precede